Polarization Independent Achromatic Meta-Lens Designed for the Terahertz Domain - Gao, Yufei; Gu, Jianqiang; Jia, Ridong; Tian, Zhen; Ouyang, Chunmei; Han, Jiaguang; Zhang, Weili (Frontiers in Physics, 2020)
In recent years, metasurface based focusing elements have gradually become an indispensable type of terahertz lenses. However, meta-lens often suffers from chromatic aberration due to the intrinsic dispersion of each element, especially in the broadband application scenarios. In this paper, we design and demonstrate a silicon based achromatic meta-lens working from 0.6 THz to 1.0 THz, which is polarization insensitive because of the adopted symmetrical structures. The simulated focal length and the full width at half maximum (FWHM) of the foci at different frequencies prove the achromatic behavior of our meta-lens, compared with the chromatic counterpart. We also point that the focus shift incongruence with our design is due to the amplitude distribution of the meta-lens. This article not only provides an achromatic planar lens working at terahertz domain, but also reveals the importance of the amplitude distribution in the achromatic metasurface design.